Evaluasi Efektivitas Belanja Modal Pembangunan Sumur Bor Pada Dinas PUPR Provinsi Nusa Tenggara Timur - Angelia Febrianti Mooy; M. E. Perseveranda; Susana Purnamasari Baso (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2025)
This study focuses on the low infrastructure index and Human Development Index (HDI) in East Nusa Tenggara (NTT), indicating an urgent need for access to clean water. The objective of the research is to evaluate the effectiveness of capital expenditure by the Public Works and Housing Office (PUPR) of NTT Province in the development of borewell infrastructure. Data were collected through interviews and official documents, including budget realization reports and project package lists. The results indicate that the budget allocation for borewell construction is significant and close to the budget ceiling, reflecting the local government's commitment. The financial effectiveness of capital expenditure is very good, with most projects rated as